EXERCISE STIMULATES IL-15 AND REGULATES SKIN METABOLISM AND AGING: A LITERATURE REVIEW - Diah Kartika; Nila Wahyuni (Program Studi Magister Fisiologi Keolahragaan, Fakultas Kedokteran, Universitas Udayana, 2023)
Background: Aging is an inevitable process across the human’s life and it results from cumulative cellular-level damage and changes in the genetic program. Research has also studied the role of immunology in improving skin metabolism, including the involvement of interleukin (IL)-15 induced by exercise in modifying skin response. Our paper will focus on discussing the benefit of exercising on how it affects the release of IL-15 on a molecular level and the impact it has on both skin metabolism and the aging process. Methods: We performed literature searching in several online databases such as PubMed, EMBASE, CENTRAL, and Google Scholar. We performed searching using (exercise) AND (interleukin-15) OR (skin aging) to find eligible literature. We create a narrative review to discuss the effect of exercise in stimulating IL-15 and regulates skin metabolism and aging. Discussion: Some mechanisms are proposed to contribute to the aging process, including the role of telomeres, DNA damage, and the immune system. One of the recent cytokines being studied is interleukin-15. This proinflammatory factor is induced by exercises and it exerts its cellular effect through multiple pathways, including JAK-STAT, PI3K-AKT/mTOR, Ras-RAF/MAPK, and AMPK. Additionally, certain regimens of exercise may provide different changes in the IL-15 levels. On the other hand, physical activities may also provide benefits to the skin through the production of NAD+ and collagen synthesis. Conclusion: The mechanism on which exercises might be beneficial could be seen through the IL-15 changes, collagen synthesis, and NADH production. Further studies are required to identify the appropriate exercise prescription to maximize the skin health benefit as well as the other parameters of skin aging to better understand the role of exercise in this process of countering aging. Keywords: aging; exercise; interleukin-15; skin metabolism